Prevalence and associated factors of postpartum anemia after cesarean delivery in public hospitals of Awi zone, North West Ethiopia, 2023; a cross-sectional study - Gebretsadek Habtamu; Asmare Talie; Tinsae Kassa; Dawit Misganaw Belay (PLoS ONE, 2025)
Background Anemia is a serious global public health problem, especially in developing nations. Anemia during pregnancy is appropriately recognized, whereas postpartum anemia especially after cesarean delivery in Ethiopia has received very little attention. Due to this it leads to poor quality of life, palpitations, an increase in maternal infections, exhaustion, diminished cognitive function and postpartum depression. Therefore, this study aimed to assess the prevalence and associated factors of postpartum anemia after cesarean delivery in public hospitals of Awi zone, North West Ethiopia, 2023. Method A hospital-based cross-sectional study was conducted among 395 mothers who gave birth by cesarean delivery from May 1–30, 2023. Data were collected using a pretested checklist. A simple random sampling technique was used to select study participants. Then the data were entered into EPI-data version 4.6 and exported to the SPSS version 25 for analysis. A logistic regression model was fitted to assess the association between outcome and explanatory variables. Variables with a p-value of 0.25 or less in bivariable analysis were candidates for multivariable analysis and P-value < 0.05 in multivariable analysis was considered to declare a result as statistically significant in this study. Result The prevalence of postpartum anemia after cesarean delivery was 18.9% (95% CI (15.1, 23.1)) with a response rate of 97.97%. Being primipara (AOR = 0.47,95%CI = 0.24,0.92), indication for current C/S (malpresentation) (AOR = 0.29,95%CI = 0.09,0.90), having pre-operation hemoglobin level <11g/dl (AOR = 14.5;95% CI = 4.11,51.16) and having medical complication during current pregnancy (AOR = 5.95,95%CI = 1.88,18.83) were significantly associated with postpartum anemia after cesarean delivery. Conclusion The findings of the study show that the prevalence of postpartum anemia after cesarean delivery is a mild public health problem. Therefore, promoting the benefits of early detection and management of pregnancy complications such as predelivery anemia and medical complications is crucial.